Size-controlled fabrication of zein nano/microparticles by modified anti-solvent precipitation with/without sodium caseinate - Li F (Dove Medical Press, 2017)
Feng Li,1 Yan Chen,1,2 Shubo Liu,1 Jian Qi,1 Weiying Wang,1 Chenhua Wang,1 Ruiyue Zhong,1 Zhijun Chen,1 Xiaoming Li,1 Yuanzhou Guan,1 Wei Kong,1,2 Yong Zhang1,2 1National Engineering Laboratory for AIDS Vaccine, School of Life Sciences, Jilin University, Changchun, 2Key Laboratory for Molecular Enzymology and Engineering, the Ministry of Education, School of Life Sciences, Jilin University, Changchun, China Abstract: Zein-based nano/microparticles have been demonstrated to be promising carrier systems for both the food industry and biomedical applications. However, the fabrication of size-controlled zein particles has been a challenging issue. In this study, a modified anti-solvent precipitation method was developed, and the effects of various factors, such as mixing method, solvent/anti-solvent ratio, temperature, zein concentrations and the presence of sodium caseinate (SC) on properties of zein particles were investigated. Evidence is presented that, among the previously mentioned factors, the mixing method, especially mixing rate, could be used as an effective parameter to control the size of zein particles without changing other parameters. Moreover, through fine-tuning the mixing rate together with zein concentration, particles with sizes ranging from nanometers to micrometers and low polydispersity index values could be easily obtained. Based on the size-controlled fabrication method, SC-coated zein nanoparticles could also be obtained in a size-controlled manner by incubation of the coating material with the already-formed zein particles. The resultant nanoparticles showed better performance in both drug loading and controlled release, compared with zein/SC hybrid nanoparticles fabricated by adding aqueous ethanol solution to SC solution. The possible mechanisms of the nanoprecipitation process and self-assembly formation of these nanoparticles are discussed. Keywords: zein, phase separation, microparticle, nanoparticle, encapsulation, drug release